2022
DOI: 10.3390/ma15051638
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach to Using Sheep Wool as a Fibrous Material for Enhancing Strength and Transport Properties of Concrete Composites

Abstract: An important goal to achieve sustainable development is to use raw materials that are easily recyclable and renewable, locally available, and eco-friendly. Sheep wool, composed of 60% animal protein fibers, 10% fat, 15% moisture, 10% sheep sweat, and 5% contaminants on average, is an easily recyclable, easily renewable, and environmentally friendly source of raw material. In this study, slump testing, compressive and flexural strengths, ultrasonic pulse velocity, sorptivity, and chloride penetration tests were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…[38,56,57]-have multiple benefits, such as; low costs and abundant availability. Alyousef et al [58] reported the same for sheep wool fiber when used as dispersed reinforcement in a cementitious concrete composite to enhance the mechanical properties of said concrete composite. The incorporation of low-density (1.2-1.6 g/cm 3 ) plant fibers produces lighter composites compared to synthetic fibers.…”
Section: Introductionmentioning
confidence: 99%
“…[38,56,57]-have multiple benefits, such as; low costs and abundant availability. Alyousef et al [58] reported the same for sheep wool fiber when used as dispersed reinforcement in a cementitious concrete composite to enhance the mechanical properties of said concrete composite. The incorporation of low-density (1.2-1.6 g/cm 3 ) plant fibers produces lighter composites compared to synthetic fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Natural fiber composites are widely used in many fields due to their superior mechanical properties. The use of waste and natural fibers is extremely important in terms of environmental sustainability and cost (Alyousef et al, 2022a(Alyousef et al, , 2022b. Recently, there has been a significant increase in the amount of studies in this field (Fiore et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that acoustic properties of the produced materials depend on their structure and parameters. In the search of cheap and ecofriendly materials in the building industry, researchers were also produced sheep wool fiber reinforced concrete composite materials and, investigated their structural and mechanical properties (Alyousef et al, 2020;Alyousef et al, 2022aAlyousef et al, , 2022bFantilli and J o zwiak-Nied zwiedzka, 2020;Fiore et al, 2020;J o zwiak-Nied zwiedzka and Fantilli, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Such products can be used in the construction of pavements and overlays or concrete structures. For example, natural, synthetic, and industrial fibers such as steel fibers, 1–5 jute and kenaf fiber, 6–8 rice fiber, 9 glass fiber, 10–12 basalt fiber, 13 wool of animals, 14,15 and Forta aramid fibers 16–20 have been employed in previous works in the mix design of concrete materials. Review of literature also reveals that other industrial waste materials such as recycled stone and metal aggregates, rubber powders and granules, shredded PET, furnace slag aggregates, and powders are possible candidate materials to be utilized in the mix design of asphalt or concrete materials 21–29 …”
Section: Introductionmentioning
confidence: 99%